Executive summary of the joint position paper on renal denervation of the Cardiovascular and Interventional Radiological Society of Europe and the European Society of Hypertension. Issue 12 (December 2016) - Moss, Jonathan G.; Belli, Anna-Maria; Coca, Antonio; Lee, Michael; Mancia, Giuseppe; Peregrin, Jan H.; Redon, Josep; Reekers, Jim A.; Tsioufis, Costas; Vorwerk, Dierk; Schmieder, Roland E.
Abstract : Renal denervation (RDN) was reported as a novel exciting treatment for resistant hypertension in 2009. An initial randomized trial supported its efficacy and the technique gained rapid acceptance across the globe. However, a subsequent large blinded, sham arm randomized trial conducted in the USA (to gain Food and Drug Administration approval) failed to achieve its primary efficacy end point in reducing office blood pressure at 6 months. Published in 2014 this trial received both widespread praise and criticism. RDN has effectively stopped out with clinical trials pending further evidence. This joint consensus document representing the European Society of Hypertension and the Cardiovascular and Radiological Society of Europe attempts to distill the current evidence and provide future direction and guidance.